Multifunctional Utilization of Marble Wastes in One-Part and Two-Part Geopolymer Production Methods: Applications as Filler and Fine Aggregate - Bodur, Burak; İşik, Muhammet Ahmet Mecit; Kaplan, Gökhan; Bayraktar, Oğuzhan Yavuz (Kastamonu University, 2025)
This study compares the one-part and two-part geopolymer production methods, both of which utilise marble powder as a filler material. Marble powder, when used as a filler, is a promising strategy that can significantly enhance the environmental sustainability of construction materials and reduce carbon emissions. The study produced different geopolymer mixtures by replacing ground granulated blast-furnace slag (GBFS) with marble powder at 0% and 30% levels and using sodium metasilicate as an activator. These mixtures' mechanical properties, workability, bulk density, water absorption, and compressive strength were evaluated, with a specific focus on the role of marble powder as a filler material. The results indicate that the addition of marble powder decreases the viscosity of the geopolymer mixtures, with the one-part method exhibiting increased fluidity. However, it was observed that adding marble powder reduced compressive strength. In contrast, the mixtures produced by the two-part method, while more costly, provided materials with a high degree of reliability in their resistance to elevated temperatures and mechanical loads, demonstrating higher durability and thermal stability. The one-part method, with its increased fluidity, offers a practical and easily applicable solution, while the two-part method, despite its higher cost, provides materials with superior resistance to elevated temperatures and mechanical loads. However, both methods offer the unique advantage of significantly reducing carbon emissions when marble powder is used. These findings suggest that marble powder can be used in the production of sustainable construction materials, and the two different production methods offer distinct advantages.
Keywords: Carbon emissions; Environmental sustainability; Marble powder; Geopolymer production methods; Construction Materials; Yapı Malzemeleri; Geopolimer Üretim Yöntemleri; Çevresel Sürdürülebilirlik; Karbon Emisyonları; Mermer Tozu